Safeguarding Intangible Cultural Heritage by Creating Meaningful Transmission Experiences. Issue 1 (March 2015) - Mitchenson, Donna
This research analyses and reviews new and existing applications of novel technologies in heritage settings. This essay reviews current trends in heritage technologies and highlights their potential in safeguarding and transmitting intangible cultural heritage. True safeguarding of intangible cultural heritage is in creating meaningful transmission experiences. Modes of transmission have become tired, static and fail to pair with modes of learning. The term 'meaningful transmission experience' describes situations where heritage communications are optimized using established learning modes to enhance novel technologies. This research by no means covers all applications of safeguarding and the transmission of intangible cultural heritage, but instead concentrates on the intangible aspects of built heritage. The future of intangible cultural heritage lies in communicating heritage effectively. It is my recommendation that coupling novel technologies with established learning styles will enrich user experience. Further, this will enable intangible cultural heritage to remain current with society.